2019
DOI: 10.1021/acs.jpcc.9b05376
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Substitution of Hollandite α-MnO2: Enhanced Potential and Structural Stability on Lithiation from First-Principles Calculation

Abstract: Hollandite α-MnO2, consisting of manganese–oxygen octahedra, has recently attracted attention due to its high theoretical capacity, yet it suffers capacity degradation during repeated (de)­lithiation. Here we use a new conceptual approach to substitute one of the Mn in the tunnel wall via the form of Mn0.875M0.125O2 (M = Ti, V, Cr, Nb, Ru), aiming to increase the lithiation potential and attain the theoretical capacity via the enhanced structural stability, with the ultimate goal of improved capacity retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 56 publications
4
47
0
Order By: Relevance
“…To gain some understanding on the possible origin of surface dissolution of MnO 2 during the discharge, we purposely selected the nanorods that had undergone relatively low level dissolution even at the depth of discharge of ≈40% (i.e., three electron equivalents). [21] Mn 3+ ion is the strong Jahn-Teller active species that induces its structural distortion. [22] In our system, as we expect either Zn 2+ or H + ion insertion on the surface, the guest ion may more likely be H + ions than Zn 2+ ions as no clear Zn signal was detected from the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain some understanding on the possible origin of surface dissolution of MnO 2 during the discharge, we purposely selected the nanorods that had undergone relatively low level dissolution even at the depth of discharge of ≈40% (i.e., three electron equivalents). [21] Mn 3+ ion is the strong Jahn-Teller active species that induces its structural distortion. [22] In our system, as we expect either Zn 2+ or H + ion insertion on the surface, the guest ion may more likely be H + ions than Zn 2+ ions as no clear Zn signal was detected from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…This change in interplanar spacing may be attributed to distortion of a MnO 2 unit cell due to Mn valence reduction from guest ion insertion as in the case of lithiation of α‐MnO 2 . [ 21 ] Mn 3+ ion is the strong Jahn–Teller active species that induces its structural distortion. [ 22 ] In our system, as we expect either Zn 2+ or H + ion insertion on the surface, the guest ion may more likely be H + ions than Zn 2+ ions as no clear Zn signal was detected from the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20−26 Density functional theory (DFT) has been used to explore transition-metal substitution of Mn in the tunnel wall for use as cathode materials in Li-ion batteries. 27 In each case, it was assumed that the substituted transition metal was oxidation state 4+ and indicated some promise for increased stability on lithiation. 27 Incorporation of V into the α-MnO 2 structure has been of particular interest due to its similar atomic radius (V 5+ , 0.53 Å) to Mn 4+ (0.54 Å), potential for electrochemical activity, and the lack of a Jahn−Teller distortion upon reduction of the vanadium ion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consistent with the experimental observations, DFT simulations also reveal the substituted V ions to be in a slightly oxidized state and that upon lithiation V is reduced only slightly as compared to Mn. In a former theoretical paper, [5] it is predicted that there might be two possible structural evolution mechanism upon lithiation. In our ex-situ study on lithiated samples, we observed the evidence for both evolution mechanisms.…”
mentioning
confidence: 99%